2010
DOI: 10.1074/jbc.m110.133579
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Transcription Factor Nrf2 Negatively Regulates Autophagy and Growth Arrest Induced by the Anticancer Redox Agent Mitoquinone

Abstract: Mitoquinone (MitoQ) is a synthetically modified, redox-active ubiquinone compound that accumulates predominantly in mitochondria. We found that MitoQ is 30-fold more cytotoxic to breast cancer cells than to healthy mammary cells. MitoQ treatment led to irreversible inhibition of clonogenic growth of breast cancer cells through a combination of autophagy and apoptotic cell death mechanisms. Relatively limited cytotoxicity was seen with the parent ubiquinone coenzyme Q 10. Inhibition of cancer cell growth by Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 58 publications
14
134
1
1
Order By: Relevance
“…This indicated that Nrf2 was responsible for regulating basal levels of autophagy in U251 cells. Our finding was in concordance with previous reports in other tumors (35). Nevertheless, from our point of view, further investigation still needs to be done because Nrf2-responsive genes that stimulate autophagy are not well known.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicated that Nrf2 was responsible for regulating basal levels of autophagy in U251 cells. Our finding was in concordance with previous reports in other tumors (35). Nevertheless, from our point of view, further investigation still needs to be done because Nrf2-responsive genes that stimulate autophagy are not well known.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, how Nrf2 regulates autophagy remains unknown. Others have also reported that Nrf2 negatively regulated autophagy induced by anticancer redox agent MitoQ and the Nrf2-regulated enzyme NQO1 was partly responsible for adjusting the level of autophagy (35).…”
Section: Discussionmentioning
confidence: 96%
“…They comprise enzymes that directly or indirectly exert antioxidant functions (5,21,111,202,264,373,491), molecular chaperons (265), and proteins that enhance GSH synthesis and regeneration (164,174,210,276,330,336), phase 2 detoxication, drug metabolism (169,210,326,392,424,479), recognition, repair, and removal of damaged proteins (191,264,265,393), and nucleotide excision repair (8), further proteins that regulate the expression of other transcription factors, growth factors, and receptors (113,163), and inhibit cytokine-mediated inflammation (6,209,245,385,503) and autophagy (394). With its broad range of target genes, Nrf2 is certainly one of the most important transcription factors that protect the organism against exogenous stressors, be they poisonous food ingredients, physical damage, or infection.…”
Section: B the Physiological Context Of Nrf2-dependent Gene Activationmentioning
confidence: 99%
“…Nrf2 appears to be involved in the regulation of protein aggregation in autophagic substrate selection (43) as well as autophagy per se (44)(45)(46)(47). Although it remains unclear whether the observed increased steady state levels of autophagosomes in Nrf2-deficient breast cancer cells, endothelial cells, and airway epithelial cells are caused by an impairment of autophagosome clearance (44,46,47), it has been demonstrated that Nrf2 is a critical mediator of autophagic clearance of ubiquitinated protein aggregates in macrophages (45).…”
Section: Nrf2 In Autophagymentioning
confidence: 99%
“…Although it remains unclear whether the observed increased steady state levels of autophagosomes in Nrf2-deficient breast cancer cells, endothelial cells, and airway epithelial cells are caused by an impairment of autophagosome clearance (44,46,47), it has been demonstrated that Nrf2 is a critical mediator of autophagic clearance of ubiquitinated protein aggregates in macrophages (45). In addition, a recent study showed that Nrf2 is capable of clearing phosphorylated tau by induction of nuclear dot protein 52 (NDP52), an autophagy adaptor protein (also known as CALCOCO2) in the presence of autophagy stimulator thereby potentially contributing to brain protection (48).…”
Section: Nrf2 In Autophagymentioning
confidence: 99%